2021
DOI: 10.1007/s00423-021-02193-x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion prevention after endometriosis surgery — results of a randomized, controlled clinical trial with second-look laparoscopy

Abstract: Purpose Adhesion formation after endometriosis surgery is a severe problem affecting up to 90% of patients. Possible complications include chronic pain, ileus, and secondary infertility. Therefore, effective adhesion prophylaxis is desirable, for which the adhesion barrier 4DryField® PH is evaluated in the present clinical study. It is a starch-based powder that forms a gel after irrigation with saline solution and thus separates surgical sites as physical barrier for adhesion prevention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
0
13
1
Order By: Relevance
“…We read with great attention the well-designed randomized article by Kramer et al which was published in your journal [1]. This study reports the advantages of the adhesion barrier 4DryField® PH in patients following endometriosis surgery.…”
Section: Dear Editormentioning
confidence: 99%
“…We read with great attention the well-designed randomized article by Kramer et al which was published in your journal [1]. This study reports the advantages of the adhesion barrier 4DryField® PH in patients following endometriosis surgery.…”
Section: Dear Editormentioning
confidence: 99%
“…Patient collectives and primary endpoint results of our trial are published elsewhere [26]. In summary, both groups were comparable with respect to relevant patient parameters.…”
Section: Methodsmentioning
confidence: 73%
“…No complications occurred in any of the patients during either hospital stay. Adhesions were assessed during both interventions using the same detailed adhesion score [26]. In both surgeries, 16 previously defined specific areas of interest were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies in the field of gynecology and the use of starch mainly concern the prevention of adhesions, which is an undoubted advantage of 4DryField. Kramer et al showed that the use of 4DryField in endometrial cyst surgery reduces the formation of adhesions by 85% [ 43 ]. On the other hand, studies by Ziegler et al showed that it is safe from the risk of inflammation and is good at preventing the formation of adhesions despite the increase in C-reactive protein levels after surgery [ 44 ].…”
Section: Discussionmentioning
confidence: 99%